Embodied water analysis of higher education buildings using an input-output-based hybrid method. (10th September 2022) - Dixit, Manish Kumar; Kumar, Pranav Pradeep; Haghighi, Omid
Abstract: From the production of raw materials to the construction of a building, construction activities consume large quantities of water as embodied water. In fact, over 16% of global water use occurs in construction activities. Total embodied water of a building includes water directly used in construction activities, water indirectly consumed in the production and delivery of construction materials, and water used by the energy sources powering the construction activities as embodied energy. However, the number of comprehensive studies on embodied water of buildings is lacking. In this study, an input-output-based hybrid model is developed to determine and analyze not only direct and indirect embodied water intensities, but also the energy related embodied water intensities of construction materials and higher education buildings. The results indicate that, similar to embodied energy, using an aggregated input-output-based hybrid analysis may return misleading embodied water values as compared to a disaggregated analysis because embodied water intensities vary for each material. The results also show that the amount of energy related embodied water could be significant (7%–12% of total embodied water at the building level), highlighting the significance of energy related water use when evaluating total embodied water. Results further underscore the significance of applying a more energy-water nexus perspective when evaluating the environmental and resource consumption impacts of buildings.